Implementasi Pendekatan Eklektik berbasis Sharing Zone - Muhammad Mushfi El Iq Bali; Lailatur Rohmah (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2018)
This research aims to determine the effort of guidance in implementing an eclectic approach to foster children. This research was conducted because some students who have difficulty in facing life problems in boarding schools. Through this Sharing Zone activity, students can share story with guidance so they can relieve and solve the problem well. The guidance can provide guidance and direction to their students so that they can be more enthusiastic in undergoing some tiring activities and overcome some problems of their life in Islamic boarding schools. Various personalities of students in boarding schools give some little difficult for guidance to face their students. The Eclectic Approach based on Sharing Zone in Nurul Jadid Islamic Boarding School exactly Al-Hashimiyah Region really produces maximum results. So that the learning spirit existence of students will be maintained in undergoing the intense activities.